Knowledge, attitude, and practices towards exclusive breastfeeding among lactating mothers attending the selected Health Center III in Mubende district. - Nakimuli, Jackline; Okoth Ogenda, Constantine (Student's Journal of Health Research Africa, 2025)
Background: Exclusive breastfeeding means that an infant receives only breast milk, no other liquids or solids are given, not even water, except for oral rehydration solutions, drops, or syrups of vitamins, minerals, or medicines when necessary. (WHO, 2023). Objectives of the study: To find out the level of knowledge towards exclusive breastfeeding among lactating mothers attending selected health center IIIs in Mubende District; to assess attitude towards exclusive breastfeeding among lactating mothers attending selected health center IIIs in Mubende District, and to determine the practices towards exclusive breastfeeding among lactating mothers attending selected health center IIIs in Mubende District. Methods: A descriptive random cross-sectional method was used to obtain data from 246 participants who were women of reproductive age (15-49) years with infants 0-6months, the study was conducted at Mubende District, located 138.3 km from Kampala, the capital city, via the Mityana - Mubende road. Results: The study found neutral knowledge on exclusive breastfeeding among lactating mothers in Mubende district (mean = 2.960 and SD = 0.855) and a neutral attitude towards exclusive breastfeeding (mean = 3.259 and SD = 0.650). Despite their neutral knowledge and attitude, the lactating mothers practice good exclusive breastfeeding (mean = 3.100 and SD = 1.032). Conclusion The study showed average knowledge, attitude, and practice of exclusive breastfeeding among lactating mothers in Mubende district. Recommendation: Health authorities in Mubende district strengthen health education to increase knowledge of lactating mothers on exclusive breastfeeding and to increase sensitization of mothers to attend antenatal services where they can obtain knowledge and other benefits related to maternal and child health.